UWB elliptical patch monopole antenna with dual-band notched characteristics - A H Majeed; K H Sayidmarie (International Journal of Electrical and Computer Engineering (IJECE), 2019)
In this paper, a new approach to the design of an UWB monopole antenna with dual band-notched characteristics is presented.   The antenna has the form of an elliptical monopole over a ground plane having an elliptical slot to achieve the UWB. The dual-band notch function is created by inserting a U-shaped and a C-shaped slots on the radiating patch, thus no extra size is needed. The proposed antenna shows a good omnidirectional radiation pattern across the band from 3.2 to more than 14 GHz. The dual band-rejection is for 4.88-5.79GHz centered at 5.4GHz and 7.21-8.46 GHz centered at 7.8 GHz. The antenna prototype using the FR-4 substrate with εr=4.3 has a compact size of 25mm×25 mm ×1.45mm. The fabricated prototype showed experimental results comparable to those obtained from the simulations.